6: PALLIATIVE GASTRECTOMY FOR METASTATIC GASTRIC ADENOCARCINOMA: A NATIONAL POPULATION-BASED COHORT STUDY. (23rd April 2022) - Kamarajah, S; Markar, S; Phillips, A; Salti, G; Dahdaleh, F; Griffiths, E
Abstract: Background and aim: The impact of palliative gastrectomy for metastatic gastric adenocarcinoma, especially by site of metastasis remains unclear. This study aimed to evaluate the long-term outcomes of palliative gastrectomy for metastatic gastric adenocarcinoma. Methods: The National Cancer Database (2010–2015) was used to identify patients with clinical metastatic (cM1) gastric adenocarcinoma (n = 19, 411) at diagnosis. The main variable was index management for cM1 gastric adenocarcinoma (i.e. no treatment, palliative chemotherapy or palliative gastrectomy). Cox multivariable analyses were used to account for treatment selection bias. Results: Of 19, 411 patients, 10, 893 (56%) received palliative chemotherapy, and only 1, 101 (6%) received palliative gastrectomy only. The median survival was 6.1 months, and 5-year survival was 4% in the entire cohort. Patients receiving palliative gastrectomy had a significantly longer survival than patients without any treatment or palliative chemotherapy (median: 12.8 vs 1.8 vs 9.5 months, P < 0.001), which remained after multivariable adjustment (HR: 0.30, CI95%: 0.28–0.33, P < 0.001). Stratified analyses by clinical nodal stage (cN) demonstrated survival benefit with palliative gastrectomy: cN0 (HR: 0.28, CI 95%: 0.24–0.32), cN1 (HR: 0.27, CI 95%: 0.23–0.31), cN2 (HR: 0.29, CI 95%: 0.24–0.37), and cN3 (HR: 0.26, CI 95%: 0.20–0.32). Palliative gastrectomy remained superior compared to palliative chemotherapy for metastatic disease limited to liver, bone and peritoneum, but equivalent to lung metastasis and inferior to brain metastasis. Conclusion: Palliative gastrectomy appears to have a modest survival benefit over palliative chemotherapy alone. Differences in outcomes by site of metastasis warrant further research to understand tumor biology and identify specific subgroups which may benefit from palliative gastrectomy.